RELEVANSI PEMIKIRAN PENDIDIKAN IMAM AR-RAFI’IE DALAM KONTEKS PEMBELAJARAN MODERN - Ahmad Syauky; Warul Walidin (Yayasan An-Nur Meunara Baro, 2025)
This article explores the relevance of Imam Ar-Rafi’ie's educational thought in addressing the challenges of 21st-century modern learning. Amid the rapid advancement of technology and the shift toward competence-based and digitalized education, there is growing concern over the erosion of spiritual and moral values in educational processes. Employing a qualitative approach with a library research method, this study analyzes primary texts by Imam Ar-Rafi’ie, such as Al-Muharrar and Al-Aziz Syarh al-Wajiz, alongside secondary literature from academic journals and books published between 2018 and 2025. The findings reveal that although Imam Ar-Rafi’ie did not formulate a formal educational theory, his works convey fundamental Islamic educational principles, including the integration of knowledge and ethics, balance between naqli (revelation-based) and aqli (rational) sciences, and the central role of the teacher as a spiritual guide (murabbi). These concepts are highly relevant to contemporary education, which demands holistic approaches, character development, and Islamic digital ethics. The study recommends the application of Ar-Rafi’ie's thought in curriculum design, collaborative learning models, and teacher development programs. These insights contribute to the transformation of Islamic education systems that are rooted in tradition and responsive to modern realities.